SOCIAL INTELLIGENCE MEASURING: RETROSPECTIVE ANALYSIS - Зарубінська, І. Б. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In this article notion definition of social intelligence as a cognitive component of social competence is deliberated. The history of development of this phenomenon and experience of its experimental investigation is analyzed. The conclusion is made that today there is no single, unified instrument for measuring social intelligence: all the techniques examine quantitative and qualitative indicators of the development of its individual aspects, so should be used as complementary, and the conclusion as for the level of development of cognitive component of social competence and social intelligence as a whole should be the result of in-depth analysis of complementary and mutually checking facts